2015
DOI: 10.1590/1415-52732015000100005
|View full text |Cite
|
Sign up to set email alerts
|

Acute hypothalamic administration of L-arginine increases feed intake in rats

Abstract: ObjectiveThis study investigated the chronic (oral) and acute (hypothalamic infusion) effects of L-arginine supplementation on feed intake, body composition, and behavioral changes in rats. MethodsTwenty rats were divided into two groups treated orally for 60 days; one group received L-arginine (1 g/kg body weight) and one group received saline (1 mL/NaCl 0.9%). Daily consumption of water and food were evaluated, and weight monitored. After the oral treatment, the rats underwent stereotactic biopsy and a group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…Increased feed intake of young and growing guinea fowls following L-Arg supplementation of the diet with HB, when compared to their counterparts fed a similar diet but not supplemented with L-Arg in the present study, could be linked with the secretagogue activity of Arg inducing the release of insulin and glucagon, which influences feed intake and efficiency of utilization (Woods et al, 2006). Previous studies confirmed that NO generated via the L-Arg pathway is actively involved in feeding behavior through the hypothalamus (Malfatti et al, 2015), acts as a central mediator and physiological modulator of food intake (Mancuso et al, 2010). L-Arg infusion in rats also promoted satiety quantified by increased food intake after 24 hours from L-Arg administration (Malfatti et al, 2015).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Increased feed intake of young and growing guinea fowls following L-Arg supplementation of the diet with HB, when compared to their counterparts fed a similar diet but not supplemented with L-Arg in the present study, could be linked with the secretagogue activity of Arg inducing the release of insulin and glucagon, which influences feed intake and efficiency of utilization (Woods et al, 2006). Previous studies confirmed that NO generated via the L-Arg pathway is actively involved in feeding behavior through the hypothalamus (Malfatti et al, 2015), acts as a central mediator and physiological modulator of food intake (Mancuso et al, 2010). L-Arg infusion in rats also promoted satiety quantified by increased food intake after 24 hours from L-Arg administration (Malfatti et al, 2015).…”
Section: Discussionsupporting
confidence: 66%
“…Previous studies confirmed that NO generated via the L-Arg pathway is actively involved in feeding behavior through the hypothalamus (Malfatti et al, 2015), acts as a central mediator and physiological modulator of food intake (Mancuso et al, 2010). L-Arg infusion in rats also promoted satiety quantified by increased food intake after 24 hours from L-Arg administration (Malfatti et al, 2015).…”
Section: Discussionmentioning
confidence: 86%
“…Blood samples for this analysis were collected on the 23rd day of the observational period in groups: 1, 2; 5, 6; 9, 10; 13, 14. The level of l-arginine in plasma was not able to be determined, as the compound is metabolized rapidly and the dose we used for supplementation had been proven to be effective [19].…”
Section: Measurement Of Plasma Level Of Nicotinamidementioning
confidence: 99%